2017
DOI: 10.1159/000479103
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Myelofibrosis: Clinical Features, Course, and Outcome

Abstract: Background: Autoimmune myelofibrosis (AIMF) is an underrecognized cause of nonmalignant bone marrow fibrosis which occurs in the presence or absence of a defined systemic autoimmune disease. Patients with AIMF present with cytopenias and autoantibodies, and have a distinctive nonclonal myelofibrosis on bone marrow examination. AIMF is distinguished from primary myelofibrosis by the absence of splenomegaly, eosinophilia, or basophilia, and the absence of abnormal myeloid, erythroid, or megakaryocytic morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…No pediatric cases of primary AIMF have been reported; however, several adult cases have been published [6,7]. In 2003, primary AIMF in adults was defined by a set of diagnostic criteria: and (8) absence of a disorder known to cause myelofibrosis [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…No pediatric cases of primary AIMF have been reported; however, several adult cases have been published [6,7]. In 2003, primary AIMF in adults was defined by a set of diagnostic criteria: and (8) absence of a disorder known to cause myelofibrosis [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although the distinction between AMF and PMF is important, there is often an overlap in pathological features that results in not all diagnostic criteria being met [ 2 , 5 , 11 , 12 ]. Another factor that makes diagnosis difficult is that ANAs and rheumatoid factors are not serologically specific to AMF [ 11 ]. In particular, cases of thrombocytopenia alone, as in the present report, are difficult to differentiate from ITP, and some cases have been reported that were initially misdiagnosed as ITP [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune myelofibrosis (AIMF), introduced by Paquette et al in 1994, is a distinct clinicopathologic condition that occasionally occurs with autoimmune disorders such as SLE and RA [27]. Nonmalignant marrow fibrosis which occurs in the presence of a defined systemic autoimmune disease such as SLE or RA is termed secondary AIMF [28]. Primary AIMF, on the contrary, is a clinical condition with similar presentation to secondary AIMF but occurs in patients without a defined autoimmune disease [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative to differentiate AIMF from primary myelofibrosis (PMF), a clonal myeloproliferative neoplasm, because their clinical course, prognosis, and treatment vary markedly [30]. Bone marrow findings in AIMF include the following: variable bone marrow cellularity with reticulin and/or collagen fibrosis; absence of megakaryocytic, myeloid, or erythroid dysplasia; presence of lymphoid aggregates; and lack of osteosclerosis [28, 30, 31]. In contrast, PMF is characterized by bone marrow findings of moderate-to-severe reticulin fibrosis and the presence of megakaryocytic proliferation and atypia [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation